(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article, while highlighting the work of our great ancestor Musa al-Khwarizmi, attempts to reflect the scholar’s versatility and the importance of his incomparable legacy in the field of mathematics in the development of modern exact sciences.